KUALITAS SISTEM LAYANAN MENGGUNAKAN METODE FUZZY- SERVICE QUALITY - Johan Alfian Pradana; Ni Luh Putu Hariastuti (LPPM Universitas Bina Bangsa, 2023)
Improving the service quality system is an important role in universities. The purpose of the study was to determine the highest gap of each fuzzy- servqual dimension. Research procedures with statistical test steps, designing fuzzy methods, and designing fuzzy- servqual gaps. Determination of the highest level of expectation and expectation gaps from users of the administrative service system using fuzzy- service quality includes ASR3 codes of -2.25, RLB3 -2.2, RSP2 -2.17, EPT3 -1.99, TGB5 -1.85. The gap is the highest of each dimension.